Raspberry Pi Basic Tutorial using Android Application for Beginner User - GHAFFAR, AMIR IRFAN; Ibrahim, Muhamad Izzuddin; Ahmad, Mohamad Aiman Afiq; Ismail, Muhammad Faizal (Multidisciplinary Applied Research and Innovation, 2022)
This paper describes the ideas of development a mobile application for learning Raspberry Pi for user. Raspberry Pi is a multi-functional micro-controller. The Raspberry Pi is very small and affordable computer it not expensive than most video games, but with Raspberry Pi user can learn programming such as Phyton coding, build robots, and create all creative of amazing and beautiful projects. The Raspberry Pi is capable of doing all the things like other computer can do such as   surfing the internet, watching movies, playing games and listening music. Raspberry Pi has become widely use new modern technology such smart house and smart factory. The main aim on this project is to develop Raspberry Pi training kit with structured module, develop Android application to embedded the Raspberry Pi training and provide an example of projects that can be built in the Raspberry Pi with different levels type. This can be the platform for beginner users to learn Raspberry Pi and improve their knowledge. The mobile application that used in this project is Thunkable.